Anticorrosive properties of a green and sustainable inhibitor from leaves extract of Cannabis sativa plant: Experimental and theoretical approach - Haldhar, R.; Prasad, D.; Mandal, N.; Benhiba, F.; Bahadur, I.; Dagdag, O. (Colloids and surfaces. A, Physicochemical and engineering aspects, 2021)
[Display omitted] •Leaves extract of Cannabis sativa plant were used for the corrosion resistance.•The adsorption of inhibitor was shown by UV–vis.•Hypothetical investigations (computational) showed a very valuable report.•MD simulations agree with the experimental results. The leaves extract of the Cannabis sativaplant was used for the corrosion resistance of low carbon steel (LCS) in the acidic medium (0.5 M sulfuric acid) utilizing the weight-loss method, Tafel and EIS. The state of mixed inhibitor adsorption on the LCS surface is shown by potentiodynamic polarization. C. sativaachieved anextraordinary inhibition efficiency of 97.31 % at 200 mg/L of inhibitor concentration. SEM and AFM were used to know about the thin layer which was formed on the surface of LCS for its protection from corrosion and the adsorption of inhibitor were shown by UV–vis. spectroscopic technique. FT-IR technique confirmed the existence of functional groups and the heteroatoms exhibit in the inhibitor. Adsorbanceby the inhibitory molecules on the LCS surface followed the Langmuir adsorption isotherm. Hypothetical investigations (computational) showed a very valuable report. All acquired outcomes ensure that C. sativaleaves extract can procedure an effectualpreventing layer and restrict the corrosion procedure. The results of the molecular dynamics (MD) simulations agree with the appointed inhibition efficiencies of the experimentally.